Papel dos transposons de DNA da superfamília Tc1/mariner (TREM A-H) noreconhecimento de linhagens de fungos patogênicos do gênero Paracoccidioides - Fernanda Lourenço Alves (2012)
The genus Paracoccidioides is the agent of paracoccidioidomycosis, a systemic mycosis with restricted distribution to Latin America. Genetic polymorphism among isolates of Paracoccidioides has been widely demonstrated by different authors using different molecular techniques. Recent studies revealed the existence of two species, P. lutzii and P. brasiliensis, the first originally characterized as a cryptic species called "Pb01-like" and the last consists of three cryptic species, called S1,PS2 and PS3. Several types of molecular markers have been proposed for the characterization of cryptic species in the genus Paracoccidioides. However, most spend time and employs techniques quite laborious and/or expensive. Transposable elements have been used to understand the genetic structure of pathogenic fungi, helping to define groups phylogenetically related and of epidemiological importance. A recent study in the genome of Paracoccidioides revealed the presence of eightfamilies of DNA transposon, called TremA-H. The distribution of Trem elements varied between the three cryptic species of Paracoccidioides used (P. lutzii, PS2 and S1): TremC and H was found in all species, TremA, B and F in the cryptic species S1 and PS2; TremD was only detected in S1 and TremE only in P. lutzii. This work reports the use of polymerase chain reaction (PCR) to evaluate the useness of three markers to discriminate between the four cryptic species ofParacoccidioides: a) a primer for the indel region of hsp70 gene; 2) DNAmicrosatellite markers; 3) TremA-H. We studied 48 Paracoccidioides isolates and thirty was previously classified according to the cryptic species (10 P. lutzii; 15 S1, 3 PS2 and 2 PS3). 14 isolates could be classified as P. lutzii through the use of primers design to indel hsp70 gene. The other 34 isolates were classified as P. brasiliensis. The microsatellite markers used could not discriminate between thethree cryptic species of P. brasiliensis. The results obtained by the use of PCR for TremA-H showed that TremA, B, F and G are only found in P. brasiliensis (S1, PS2 and PS3); TremE is present only in P. lutzii; TremC and H are present in P. lutzii and P. brasiliensis (S1, PS2 and PS3). Interestingly, in P. brasiliensis, amplification of TremC and TremH showed a pattern of two bands, whereas in P. lutzii, was only oneband of 2 kb. In PS3 isolates, TremD showed a pattern of three bands. These results confirm the amplification patterns previously observed for the Trem elements and some expected pattern of bands can be useful as molecular markers in the genus Paracoccidioides.